Propuesta de integración de arquitectura de empresarial y arquitectura de seguridad metadata, Ingeniería Colombiana S.A.S. (2017)
It illustrates the advantages of implementing a business and security architecture with the most relevant frameworks today. Later, a manual is presented with the integration proposal specifying how the architecture should be constructed, providing matrices, tables and other tools necessary for The construction of the same.